2007
DOI: 10.1074/jbc.m609151200
|View full text |Cite
|
Sign up to set email alerts
|

How Tyrosine 15 Phosphorylation Inhibits the Activity of Cyclin-dependent Kinase 2-Cyclin A

Abstract: Inhibition of cyclin-dependent kinase 1 (CDK1) activity by Tyr-15 phosphorylation directly regulates entry into mitosis and is an important element in the control of the unperturbed cell cycle. Active site phosphorylation of other members of the CDK family that regulate cell cycle progression instates checkpoints that are fundamental to eukaryotic cell cycle regulation. Kinetic and crystallographic analyses of CDK2-cyclin A complexes reveal that this inhibitory mechanism operates through steric blockade of pep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
65
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(67 citation statements)
references
References 61 publications
2
65
0
Order By: Relevance
“…[33][34][35] However, to date, the mechanisms underlying the inhibition of CCND-dependent kinases by tyrosine phosphorylation have not been elucidated. Here we bring direct new evidences that phosphorylation of Y24 inhibits CDK6 activities by preventing its association with CCNDs.…”
Section: Discussionmentioning
confidence: 99%
“…[33][34][35] However, to date, the mechanisms underlying the inhibition of CCND-dependent kinases by tyrosine phosphorylation have not been elucidated. Here we bring direct new evidences that phosphorylation of Y24 inhibits CDK6 activities by preventing its association with CCNDs.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, cyclin-dependent protein kinases (CDKs) are regulated in part by inhibitory phosphorylation of conserved residues within the active site. Detailed studies with cyclin-dependent kinase 2 (CDK2) demonstrated that phosphorylation of threonine-14 and tyrosine-15 within the glycine-rich loop (GEGTYGVVY) inhibits kinase activity by interfering with peptide substrate binding and alters, but does not prevent, ATP binding (32). With the CDKs, the inhibitory phosphorylation within the ATP-binding domain is catalyzed by other kinases, whereas with BRI1 the inhibitory modification is an autophosphorylation reaction.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with the above mutant description, we found dramatically reduced CDKA;1 activity in kinase assays of DE plants ( Figure 6C). Recently, Tyr-15 phosphorylation of Cdk2 has been shown to result in reduced substrate binding of the kinase (Welburn et al, 2007). Indeed, the interaction of DE with a bona fide CDK substrate (i.e., CDC6) was reduced when compared with that of the wild-type CDKA;1 (Figures 7A and 7B).…”
Section: Online)mentioning
confidence: 96%